Physicochemical characteristics of commercial eucalyptus honeys from Southwest Casanare - Rubén Andrés Ortega-Bonilla (Ciencia y Tecnología Agropecuaria, 2016)
There are few characterization studies of Colombian honeys in the literature. It is important to know different aspects of national honeys in order to verify the compliance with the existing Colombian requirements and International regulations, but also to increase its exploitation considering its quality and distinctive features. Physicochemical parameters are basic factors that determine the final quality of honey. The objective of this research was to assess commercial eucalyptus honeys developed with Apis mellifera in the region of Villanueva (Colombia). Water activity (0.54), pH (5.02), free acidity (14.58 meq kg-1), moisture (16.45 %), color (91.65 mm PFund), electrical conductivity (81.3 mS cm-1), minerals (ash, 0.81 %), reducing sugars (69.95 %), sucrose (1.48 %), hydroxymethylfurfural (HMF, 67.29 mg kg-1), diastase activity (3.21 °Gothe), phenolic content (76.57 mg Quercetin/100 g), flavonoids (5.96 mg Gallic acid/100 g) and proline (180.68 mg kg-1) were determined in 24 honey samples following standard and usual procedures. The samples analyzed meet both national and international regulations for free acidity, moisture and HMF. No adulteration treatments were evidenced from proline content. However, the low diastase activity suggests that the honey went through some kind of overheating, probably during its storage under the high temperatures typical in the area of production. Usual estimations of phenolic and flavonoids content were detected. In conclusion, the tested samples fulfill some of the requirements for their commercialization. Hence, it would be convenient to develop a better control of the honey production process in the Southwest Casanare.